Legume seeds and colorectal cancer revisited: Protease inhibitors reduce MMP-9 activity and colon cancer cell migration. (15th April 2016) - Lima, A.I.G.; Mota, J.; Monteiro, S.A.V.S.; Ferreira, R.M.S.B.
Highlights: Inhibition of MMP-9 activity is an important anticancer strategy. Among eight studied legume species, only a few contained MMP-9 inhibitors. Their inhibitory activity was consistent with a reduction of HT29 cell migration. Lupin was the best inhibitor, while pea was the less effective. Differences found help to select legume potential for anticancer diets. Abstract: MMP-9 activity is strongly related to cancer growth and metastization. This study aimed at assessing the inhibitory potential of the major seed protein fractions from eight selected legume species towards MMP-9 activity in colon carcinoma cells. Albumin and globulin fractions were screened for MMP-9 inhibitors, using a fluorometric assay and gelatin zymography. Their effect on HT29 cell proliferation and cell migration was tested, as well as on the corresponding intrinsic cellular MMP-9 activities. Seed proteins include potent inhibitors of MMP-9, particularly low molecular mass proteins. Their effectiveness differs greatly among species, with a positive correlation detected between their inhibitory activity and the reduction in cell migration. Lupin seeds contain the most efficient MMP-9 inhibitors of all legume seeds analyzed, inhibiting both gelatinases and HT29 migration and growth, while pea seeds showed no effect. Results reveal legume protein MMPIs as novel metalloproteinase inhibitors with possible pharmacological interest. This may be important for selecting leguminous species with potential use in anti-cancer diets.